Strategi Kepemimpinan Kiai dengan Menrapkan Etos Kerja Islam Kepada Pegawai di Yayasan Darut Thalabah Sumber Kalong Bondowoso - Muwaffigirrohmah, Muwaffigirrohmah (Maddah: Journal of Advanced Da'wah Management Research, 2023)
The background to the implementation of the Islamic work ethic by the kiai to employees at the Darut Thalabah Foundation Sumber Kalong Bondowoso is a good start to instilling in teachers the spirit of work, that ethos is related to the spirit of work. And teachers not only carry out knowledge transformation but must have a reflection of life's struggles by working to meet the economic needs of life and improve their quality while working and have the ability to compete to achieve the goals of the foundation. The focus of the research is: 1) What is the kiai's leadership strategy for applying the Islamic work ethic to employees at the Darut Thalabah foundation? 2) What are the inhibiting and supporting factors for the kiai's leadership strategy in applying the Islamic work ethic to employees at the Darut Thalabah foundation? This research uses qualitative research methods with descriptive research type. Research subjects used purposive sampling. Data collection techniques using interviews, documentation and observation. The data analysis technique uses the Miles and Huberman model. Data validity uses data triangulation, sources and techniques. The results of this research are as follows: Kiai in applying the Islamic work ethic to employees has three strategies, 1) Exemplary Strategy. 2) Habituation Strategy. 3) Pesantren Activation Strategy (preparing the curriculum) to plan and determine activities for teachers regarding employee rights and leader responsibilities to subordinates.